The Effect of Scarcity Marketing, Fear of Missing Out (FOMO) and Electronic Word of Mouth (EWOM) on Music Concert Ticket Purchase Intention in Surabaya - Gymnastiara Aliefa Putri Wahyono; Fresha Kharisma (International Journal of Social, Economic, and Business, 2025)
This study investigates the influence of scarcity marketing, fear of missing out (FOMO), and electronic word of mouth (EWOM) on the purchase intention of music concert tickets in Surabaya. As the entertainment industry grows rapidly and digital promotion becomes increasingly dominant, understanding these factors is essential for effective marketing strategies. Using a quantitative approach with a survey method, this research collected data from 180 respondents aged 18 to 35 who had previously purchased concert tickets and were active social media users. The data were analyzed using multiple linear regression through SPSS to examine both simultaneous and partial effects of the independent variables on purchase intention. The findings indicate that scarcity marketing, FOMO, and EWOM simultaneously have a positive and significant effect on purchase intention. Partially, scarcity marketing strengthens consumers’ urgency to buy through limited availability and time-bound offers. FOMO also shows a positive impact, suggesting that the desire to avoid missing social experiences increases purchase likelihood. Additionally, EWOM positively influences purchase intention, emphasizing the role of online recommendations and credible user-generated information. Overall, the results highlight that digital promotional strategies incorporating scarcity cues, FOMO-driven content, and persuasive EWOM are effective in increasing concert ticket purchase intention in Surabaya